Improvement Effect of Bifidobacterium animalis subsp. lactis MH-02 in Patients Receiving Resection of Colorectal Polyps: A Randomized, Double-Blind, Placebo-Controlled Trial - Liu, Hui; Zhang, Kaige; Liu, Peng; Xu, Xuan; Zhou, Yuyang; Gan, Lihong; Yao, Ling; Li, Bin; Chen, Tingtao; Fang, Nian (Frontiers in Immunology, 2022)
Background: Postoperative symptoms, bowel dysfunction and recurrence are common problems after resection of colorectal polyps. We aimed to evaluate the efficacy of Bifidobacterium in the postoperative patients. Methods: In this single-center, randomized, double-blind, placebo-controlled trial, adults (18 to 70 years) undergoing endoscopic resection of colorectal polyps were treated with probiotics (Bifidobacterium animalis subsp. lactis MH-02, 2 × 109 colony-forming units per packet) or placebo once daily for 7 days. The primary clinical endpoint was a reduction in the mean total postoperative symptoms score within 7 days postoperatively. Secondary clinical endpoints were the single symptom scores, time to recovery of bowel function, and changes in the intestinal microbiota. This study is registered with the number ChiCTR2100046687. Results: A total of 100 individuals were included (48 in probiotic group and 52 in placebo group). No difference was seen in the mean scores between the two groups (0.29 vs. 0.43, P = 0.246). Colorectal polyps size (P = 0.008) and preoperative symptoms (P = 0.032) were influential factors for the primary endpoint. Besides, MH-02 alleviated difficult defecation (P = 0.045), and reduced the time to recovery of bowel function (P = 0.032). High-throughput analysis showed that MH-02 can help restore the diversity of intestinal microbiota, and increased the relative abundance of Bifidobacterium, Roseburia, Gemmiger, Blautia and Ruminococcus, while reduced the relative abundance of Clostridium at genus level (P < 0.05). Conclusion: In this prospective trial, MH-02 showed efficacy in patients with resection of colorectal polyps, particularly in the recovery of bowel function, and the changes in the intestinal microbiota may provide evidence for further exploration of the therapeutic mechanisms.